"PELAKSANAAN SUPERVISI KOLEGIAL BERBASIS PENDEKATAN DEVELOPMENTAL DALAM MENINGKATKAN KOMPETENSI PENGAJARAN GURU DI SMAN 15 PADANG" - Sumiarni Sumiarni; Reni Gusnita; Srina Desmira; Sufyarma Sufyarma; Rifma Rifma; Tia Ayu Ningrum (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Teacher professional competence constitutes a fundamental determinant of instructional quality across all phases of learning—from planning and implementation to evaluation. Collegial supervision rooted in a developmental framework presents a contextually grounded and democratic avenue for advancing teacher professionalism. This study investigated the implementation of developmental-based collegial supervision at SMAN 15 Padang, examining its effects on instructional competence and identifying the factors that either facilitate or constrain its execution. A qualitative approach employing a case study design was adopted. Data were gathered through participatory observation, in-depth semi-structured interviews, and document review, subsequently validated using source and technique triangulation. Analysis followed the interactive model proposed by Miles, Huberman, and Saldana (2014). Findings reveal that collegial supervision was carried out through five systematic stages: peer pairing formation, professional development mapping, technical preparation, a three-phase observation cycle, and documentation of outcomes. The collaborative approach emerged as the most frequently applied. Positive outcomes included enhanced pedagogical competence, the cultivation of professional reflection habits, encouragement of instructional innovation, and the establishment of a professional learning community. Enablers included transformational school leadership, a collegial institutional climate, and structural support systems; constraints encompassed cultural resistance among some teachers, limited constructive feedback skills, and excessive workload.